COMPARATIVE ANALYSIS OF THE ECONOMIC POTENTIAL OF THE REGIONS OF UKRAINE - GRYNIV, VOLODYMYR (Herald of Khmelnytskyi National University. Economic sciences, 2021)
The dynamics of economic growth of economically strong regions proved to be unstable under the influence of the global financial and economic crisis, which determined a significant decline in demand in commodity markets. The regions of Ukraine differ significantly in the level of technological development and the nature of economic growth. This fact determines the differentiated approach to regulating the formation of economic development.A feature that characterizes modern conditions of development is a clear diversification of economic potential of individual regions. Analysis of the level of economic development of the regions of Ukraine shows significant differences between them. Regional tensions, exacerbation of spatial problems, exacerbated by the instability of market transformations in various fields of activity, cause inconsistencies and differences in the scale and stages of transformation processes, significant regional differentiation of socio-economic development. The nature of economic development, which has a significant territorial differentiation, is reflected and causes social inequality, which is manifested in social relations to meet the living needs of people, creating normal living conditions. Of particular importance are the regional aspects of the strategy of socio-economic growth of the state. In this context, the issues of economic development of oblasts based on structural changes of sectoral, spatial and functional systems, restoration and strengthening of effective cooperation between oblasts, reduction of interregional disparities, rational use of economic potential of each region are especially relevant. For this reason, this study, based on theoretical considerations on the conditions of regional development, presents the results and conclusions of studies conducted among the regions of Ukraine, aimed at determining their economic potential and the causes of disparities in this area.
Keywords: region; economic potential; diversification; development; analysis; coefficient